GAYA KOMUNIKASI FEMINIM DAN MASKULIN DI FILM MARS MET VENUS - Nurkhalisa, Waliya; Hasmawati, Fifi; Hamandia, Muhammad Randicha (Virtu: Jurnal Kajian Komunikasi, Budaya dan Islam, 2023)
ABSTRACT“Feminine and Masculine Communication Styles in the 2017 Mars Met Venus Film”. The interesting thing that made the researchers conduct this research was about feminine and masculine communication when in a romantic relationship, and the film Mars Met Venus 2017 raised how the differences in communication between women and men. The 2017 Mars Met Venus film divides the film into two parts, namely "Part Girl" and "Part Boy" to see how each male partner views when communicating using firm and strong language while women speak in a gentle and stereotypical patriarchal tone. The purpose of this study is to find out how feminine and masculine communication styles are in different languages, such as bracelets and waves, as well as emotions and fights in the film Mars Met Venus. The method used in this research is descriptive qualitative research. The technique used in this research is content analysis. The findings from this study that can be identified are: feminine and masculine communication styles in different languages, namely: the first scene tells that women use figurative language to express what they feel, while the men in this film speak as they are, but the men try to translate requests hidden and choose to give up to maintain the relationship. Feminine and masculine communication styles in the category of rubber bands and waves, in the next scene shows the approaching period of how a man makes a sign of love then withdraws, then approaches again. When a woman feels loved, her self-esteem fluctuates like a wave. The last scene is about emotions and fights, women and men have different emotional needs, women will provide what is needed by emotions just like men, this makes each individual disappointed.